Early Detection of Digestive System Cancers: Insights from Enzymatic and Non-Enzymatic Tumour Markers : Biomarkers in Digestive System Cancer - Almohanna, Thualfeqar; Auda, Furqan Moein; Ali, Basim M. (Journal of Medical Biochemistry, 2025)
Background: Digestive system cancer is a silent yet dangerous disease and represents a major cause of death worldwide. Among these cancers, colon cancer is the second leading cause of cancer-related deaths globally. This study aimed to detect malignant cells at an early stage by analyzing biochemical indicators associated with the transformation of digestive cancer cells. Tumor markers, primarily proteins associated with malignant cells, may play a role in preventing the spread and progression of the disease. Methods: In this study, the tumor markers analyzed included carcinoembryonic antigen (CEA), α-enolase (ENO1), α-fetoprotein (AFP), and calprotectin (CP) to detect digestive system cancer. These markers were measured in serum samples obtained from sixty patients with digestive system cancer (the patient group) and sixty healthy individuals (the control group). Results: The results revealed highly significant changes (p-value < 0.00001) in the levels of CEA (56.698 ± 44.558 ng/mL), ENO1 (51.784 ± 10.395 ng/mL), AFP (116.275 ± 38.956 ng/mL), and CP (287.425 ± 33.181 ng/mL) in the cancerous group compared to the control group, suggesting their potential utility in early diagnosis. Furthermore, significant differences (p-value < 0.05) in liver enzymes and body mass index (BMI) provided additional evidence of pathological changes. Conclusions: The biomarkers investigated in this study demonstrate promising potential for early diagnosis while contributing to a deeper understanding of the biological mechanisms underlying digestive system cancers.